Doing Business 2009 - World Bank (Doing Business, 2008)
Comparing business regulation in 181 economies. Doing Business 2009 is the sixth in a series of annual reports comparing business regulations in 181 economies. Doing Business 2009 measures regulations affecting 10 areas of everyday business: Starting a business - steps, time, cost, and minimum capital to register a new business. Enforcing contracts - steps, time, and cost to enforce a commercial contract. Employing workers - indices of employment law rigidities cost of economic redundancies. Getting credit - extent of credit information sharing and creditor rights. Closing a business - steps, time, and cost to close down a business recovery rate for creditor. Registering property - steps, time, and cost to transfer ownership of commercial real estate. Protecting investors - indices on disclosure, investor suits, and standing in court. Dealing with construction permits - steps, time, and cost of business inspections and licensing. Paying taxes - statutory rates, number of taxes paid, and number of hours spent on preparing tax returns. Trading across borders - steps, time, and number of documents necessary to export and import. Doing Business 2009 updates all sets of indicators, ranks economies on their overall ease of doing business, and analyzes reforms to business regulation - identifying identifying which countries are improving the most. The indicators are used to analyze economic outcomes and identify what reforms have worked, where and why. Doing Business 2009 focuses on how complex business regulations can impact business growth and job creation